Operationalising Islamic Moderation in Digital Communication: Ethical Pathways to Counter Social Polarisation in Indonesia - Suhantoro, Suhantoro; Syahrudin, Syahrudin; Susanto, Roni; Lailatul Qomariyah, Darul (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
Social polarization in Indonesia's digital age is increasingly shaped by the fragmentation of micro-identities and the algorithmic dynamics of social media platforms. However, existing studies tend to emphasize technological or political factors while underexploring the ethical-religious dimensions that can counter such polarization. In particular, the role of moderate Islamic values ​​as a normative and communicative framework for digital interactions remains under-theorized and under-examined empirically. To address this gap, this study investigates how Islamic principles of moderation (wasatiyyah) can be operationalized in digital communication practices to reduce polarization and strengthen social cohesion. Using a qualitative case study design, data were collected through in-depth structured interviews with 18 participants, including Islamic religious leaders, sociologists, and active social media users, selected based on their engagement with online religious and social discourse. These interviews were complemented by a systematic content analysis of 120 social media posts and discussions across major platforms, which were analyzed using thematic coding to identify patterns of ethical expression, interaction styles, and conflict framing. The findings demonstrate three analytical contributions. First, the digital articulation of Islamic values ​​such as ukhuwah (social solidarity), adab (ethical behavior), and tawasuth (politeness) serves as a counter-discursive mechanism that disrupts polarizing narratives by reframing disagreements in moral and relational terms, rather than identity-based antagonisms. Second, these values ​​shape inclusive communication practices such as dialogical engagement, self-restraint in judgment, and recognition of differences that reduce symbolic exclusion and soften ideological boundaries in online interactions. Third, the integration of moderate Islamic ethics with digital modernity produces a form of moral resilience that enhances social cohesion by balancing religious norms with the participatory logic of digital media